Indeterminate Roots: Learning to Teach with Kafka (Konturen, 2026)
Kafka's short prose pieces often challenge our ability to decipher them, sometimes, seemingly, in inverse proportion to their brevity. This essay takes "The Trees" [Die Bäume] as an exploratory guide towards meeting that challenge, entertaining different reading methods that emerge through classroom discussion, methods that the text seems to both demand and disavow: ones that turn toward Kafka’s unsettled Jewish-Hebraic and European heritage, ones that invite students’ own experience, and ones that probe the nature of language itself. As a template of the reading process, and of teaching that process in turn, Kafka's text points to a shared interpretive practice that may connect us to others while simultaneously enabling us to question who "we" really are.
Keywords: Stamm; Boden; appearance; interpretation; reading